Prevalence, socio-demographics and service use determinants associated with disclosure of HIV/AIDS status to infected children: a systematic review and meta-analysis by 1985-2021 - Bahram Armoon; Marie-Josée Fleury; Peter Higgs; Amir-Hossien Bayat; Azadeh Bayani; Rasool Mohammadi; Elaheh Ahounbar (BMC, 2022)
Abstract Background Human immunodeficiency virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) is a public health issue of global importance. To our knowledge, no previous meta-analysis documenting the prevalence, socio-demographic, and service use determinants associated with HIV/AIDS disclosure to infected children has been conducted. The present study aimed to determine the prevalence, socio-demographics and service use determinants associated with the disclosure of HIV/AIDS status to infected children. Methods Studies in English published between 01 January 1985 and 01 November 2021, and available on PubMed, Scopus, Web of Science, and Cochrane electronic databases were searched. After reviewing for study duplicates, the full-text of selected articles were assessed for eligibility using Population, Intervention, Comparator, Outcomes (PICO) criteria. We used fixed and random-effects meta-analysis models to estimate the pooled prevalence, pooled odds ratio (OR), and 95% confidence intervals. Results After article duplicates were excluded, assessments of abstracts were completed, and full-text papers evaluated, 37 studies were included in this meta-analysis. The prevalence of the disclosure of HIV status to children was measured to be 41% in this research. The odds that a child of 10 years and older is informed that they are HIV-positive is 3.01 time the odds that younger children are informed. Those children who had primary or lower schooling level were 2.41 times more likely to be informed of their HIV-positive status than children with higher levels of schooling. Children who had a non-biological parents were 3.17 times more likely to have been disclose being HIV-positive; social support (OR = 8.29, 95%CI = 2.34, 29.42), children who had higher levels of social supports were 8.29 times more likely to disclose HIV-positive; the primary educational level of caregivers (OR = 2.03, 95%CI = 1.43, 2.89), respondents who had caregivers with primary education level were 2.03 times more likely to disclose HIV-positive; antiretroviral treatment (ART) adherence (OR = 2.59, 95%CI = 1.96, 3.42), participants who adhered to ART were 2.59 times more likely to disclose HIV-positive and hospital follow-up (OR = 2.82, 95%CI = 1.85, 4.29), those who had hospital follow-up were 2.82 times more likely to disclose HIV-positive; were all significantly associated with the disclosure of HIV/AIDS status to infected children. Conclusion Such data are of importance for healthcare pediatrics HIV care professionals. Facilitating HIV diagnosis and disclosure to the infected children and ensuring access to HIV treatment will likely prevent secondary HIV transmission. Healthcare professionals are expected to provide age-appropriate counseling services to this population.